1991
DOI: 10.1113/jphysiol.1991.sp018402
|View full text |Cite
|
Sign up to set email alerts
|

Salivary secretion and grooming behaviour during heat exposure in freely moving rats.

Abstract: SUMMARY1. At neutral (24°C) and at hot (40°C) ambient temperatures (TR) salivary secretion from the submandibular gland of freely moving rats was recorded, together with simultaneous observation of saliva-spreading behaviour (grooming).2. At a Ta of 24°C, basal salivary flow was less than 2 /tl/min. When rats were first placed in the experimental chamber, brief grooming bouts often occurred. Transient secretion at more than 10 ,l/min was associated with this grooming, and the rate of salivary flow was positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 22 publications
0
19
1
2
Order By: Relevance
“…It must be emphasized that a consideration of overall system function in no way implies that regulation is accomplished by a single ''coordinator'', which is sending a unified error signal to all effector organs. Indeed, Kanosue et al (1997) summarized a number of experiments (Roberts and Mooney 1974;Kanosue et al 1991;Yanase et al 1991) which supported the original assertion of Satinoff (1978, p. 75) that multiple thermoregulatory effectors are controlled by different and relatively independent neuronal circuits and emphasized the existence of separate autonomic and behavioral systems. The current proposal is compatible with these views.…”
Section: Introductionmentioning
confidence: 74%
“…It must be emphasized that a consideration of overall system function in no way implies that regulation is accomplished by a single ''coordinator'', which is sending a unified error signal to all effector organs. Indeed, Kanosue et al (1997) summarized a number of experiments (Roberts and Mooney 1974;Kanosue et al 1991;Yanase et al 1991) which supported the original assertion of Satinoff (1978, p. 75) that multiple thermoregulatory effectors are controlled by different and relatively independent neuronal circuits and emphasized the existence of separate autonomic and behavioral systems. The current proposal is compatible with these views.…”
Section: Introductionmentioning
confidence: 74%
“…• C, T b increases and saliva is spread on the skin (99,398). It has been demonstrated that thermolytic salivation is initiated when T b reaches 39…”
Section: Role Of Peripheral No In Nonevaporative Heat Lossmentioning
confidence: 97%
“…NO has been reported to be involved in this thermolytic process (Table 2), affecting weight and blood content of the salivary glands, which are the main effectors of such a thermolytic response (99,398).…”
Section: Role Of Peripheral No In Nonevaporative Heat Lossmentioning
confidence: 99%
“…In freely moving rats, the thresholds of body core temperature for grooming and the salivary secretion are similar. However, there was no correlation between the incidence of the grooming and the rate of salivary flow 55) . Therefore, the two mechanisms may be independent: there are no neurons which synchronize the activation of grooming and salivary secretion.…”
Section: Evaporative Heat Lossmentioning
confidence: 82%